The Slow Component of Oxygen Uptake and Efficiency in Resistance Exercises: A Comparison With Endurance Exercises - Garnacho-Castaño, Manuel V.; Albesa-Albiol, Lluis; Serra-Payá, Noemí; Gomis Bataller, Manuel; Felíu-Ruano, Raquel; Guirao Cano, Lluis; Pleguezuelos Cobo, Eulogio; Maté-Muñoz, José Luis (Frontiers in Physiology, 2019)
There is a lack of information regarding the slow component of oxygen uptake (VO2sc) and efficiency/economy in resistance exercises despite the crucial role played in endurance performance. Purpose: this study aimed to compare the VO2sc, efficiency/economy, metabolic, cardiorespiratory responses, rating of perceived effort and mechanical fatigue between cycling and half-squat (HS) exercises during a constant-load test at lactate threshold (LT1) intensity. Methods: Twenty-one healthy men were randomly assigned in a crossover design to perform cycle-ergometer or HS tests. The order of the two cycle ergometer tests was an incremental test for determining load-intensity in watts (W) at LT1, followed by a constant-load test at the LT1 intensity. For the three HS tests, the order was a 1RM test to determine the load (kg) corresponding to the 1RM percentages to be used during the second test, incremental HS exercise to establish the load (kg) at the LT1 intensity, and finally, a constant-load HS test at the LT1 intensity. A rest period of 48 hours between each test was established. During the HS and cycle-ergometer constant-load tests, cardiorespiratory and metabolic responses were recorded. Lower limbs fatigue was determined by a jump test before and after the constant-load tests. Results: A significant exercise mode x time interaction effect was detected in VO2, heart rate, energy expenditure, gross efficiency and economy (p < 0.05). A significant and sustained VO2 raise was confirmed in HS exercise (p < 0.05) and a steady-state VO2 was revealed in cycle-ergometer. A higher gross efficiency and economy were obtained in HS test than in cycle-ergometer exercise (p < 0.001). In both exercises, a nonsignificant decrease was observed in gross efficiency and economy (p > 0.05). Lower limbs fatigue was only detected after constant-load HS test. Conclusion: Although the VO2, heart rate and energy expenditure responses were higher in cycling exercise, the constant-load HS test induced a greater VO2sc and energy expenditure raise than the cycling test in a predominantly aerobic metabolism. These results could explain a decrease observed in jump performance only after HS test. GE and economy could benefit from the eccentric phase of the HS exercise.